Perkembangan Madrasah dan Perannya dalam Pendidikan Akhlak - Ahmad Yusuf Abdurrohman; Mukh Nursikin (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
Noble character is a virtue that every Muslim should possess. The cultivation of noble character values should be taught from an early age. Madrasah (islamic school), which is an extension of Islamic education, bears the responsibility for this. The author employs the method of library research through books, journals, and other sources in writing this article. The general aim of this research is to describe what madrasah (islamic school) is and how its history has evolved from its inception until today, as well as its role in educating the moral conduct of students. It is hoped that madrasah (islamic school) can fulfill their role effectively as a place for instilling noble character values, their practical application, and serving as a role model for students to learn and apply noble conduct in their daily lives. This research shows that madrasah since its establishment has an important role in shaping the character of students.